309 Upgrading from a dual-chamber pacemaker to a cardiac resynchronization therapy defibrillator in situs inversus totalis with dextrocardia following mitral valve replacement and tricuspid annuloplasty using a left-sided approach. (8th December 2021) - Bacci, Elodi; Santoro, Amato; Sisti, Nicolò; Baiocchi, Claudia; Cameli, Matteo
Abstract: A 71-year-old female patient was referred to our centre to upgrade a dual-chamber pacemaker to a cardiac resynchronization therapy defibrillator (CRT-D) following the detection of worsened systolic function (ejection fraction: 25–30%) via transthoracic echocardiography. The patient had situs inversus totalis with dextrocardia. She had undergone mitral valve replacement and tricuspid annuloplasty in July 2019, with a concomitant left upper pulmonary lobectomy for neoplasm, detected at cardiac tomography incidentally. In January 2020, we performed an upgrade of the preexisting device to a CRT-D system because the patient developed heart failure, reduction in systolic function, and numerous nonsustained ventricular tachycardias. The right ventricular lead that had been previously implanted was extracted. To facilitate the intervention, we decided to flip the fluoroscopic image, obtained with a right-anterior oblique view, by 180 °C (right–left), creating the optical impression of a levocardial position.